A Note on Optimality Conditions for DC Programs Involving Composite Functions - Xiang-Kai Sun; Hong-Yong Fu (Abstract and Applied Analysis)
By using the formula of the ε-subdifferential for the sum of a convex function with a composition of convex functions, some necessary and sufficient optimality conditions for a DC programming problem involving a composite function are obtained. As applications, a composed convex optimization problem, a DC optimization problem, and a convex optimization problem with a linear operator are examined at the end of this paper.